2012
DOI: 10.1097/bot.0b013e3182323f2c
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Causes of Osteoporosis in Fracture Patients

Abstract: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 47 publications
(54 reference statements)
0
14
1
4
Order By: Relevance
“…The usual paradigm at osteoporosis clinics is that PTH testing should only be performed when calcium derangements are found [24][25][26]. Our study controverts that paradigm by identifying a significant number of cases of hyperparathyroidism, which would not have been identified if the usual diagnostic guidelines were followed.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The usual paradigm at osteoporosis clinics is that PTH testing should only be performed when calcium derangements are found [24][25][26]. Our study controverts that paradigm by identifying a significant number of cases of hyperparathyroidism, which would not have been identified if the usual diagnostic guidelines were followed.…”
Section: Discussioncontrasting
confidence: 70%
“…Our review of the literature revealed a number of suggested screening regimens for identifying secondary risk factors for osteoporosis, but none targeted specifically at the elderly patient at high fall and fracture risk. Moreover, suggested screening regimes were based on either diagnostic yield or expert opinion [24][25][26]. Only Tannenbaum and colleagues considered both diagnostic yield and cost although focusing on osteoporosis and fractures risk [5].…”
Section: Discussionmentioning
confidence: 99%
“…21 Using various types of intervention programs has demonstrated success, with the end goal of improving osteoporosis follow-up in high-risk patients. 1,2,4,7,8,[12][13][14][15][16][17][18][19] Our study builds on this current trend. However, most of these programs would be difficult to implement at an average hospital system, given the lack of standardization and automation.…”
Section: Discussionmentioning
confidence: 91%
“…1,2,4,[7][8][9][11][12][13][14][15][16][17][18][19][20] Despite this burden, current literature demonstrates the low rate of follow-up care received by patients experiencing fragility fractures. 1,2,4,7,8,[12][13][14][15][16][17][18][19] We chose our patient population based on recommendations from the National Osteoporosis Foundation, which states that all individuals 50 years of age experiencing fragility fractures should be evaluated and treated for osteoporosis. 21 Using various types of intervention programs has demonstrated success, with the end goal of improving osteoporosis follow-up in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pro wa dzi to jed nak do znacz nej utra ty mi ne ral nej skła do wej tkan ki kost nej, zmniej szając wy trzy ma łość me cha nicz ną ko ści i pre dys po nu jąc je do zła mań [28]. Nad miar jo nów wap nia pod le ga usu waniu wraz z mo czem (w mniej szym stop niu z żół cią), stając się przy czy ną m.in.…”
unclassified